Phase transitions in the nanopowders KTa₀.₅Nb₀.₅O₃ studied by Raman spectroscopy - Golovina, I.S.; Bryksa, V.P.; Strelchuk, V.V.; Geifman, I.N. (Functional Materials, 2013)
Raman spectra of KTa₀.₅Nb₀.₅O₃ nanopowder solid solution were obtained at the temperatures from –190°C to 600°C and investigated for the first time. The compound was synthesized by a new technology. Temperature dependences of the intensity, width and frequency of the B₁(TO₂), A₁(TO₁), B₁(TO₃), A₁(TO₃) and B₂(TO₃) modes are thoroughly analyzed. A significant expanding of the temperature ranges of all phase transitions, correlated with a spread of particle sizes is registered. It was found that an average temperature of each of the phase transitions is shifted in different way, in particular: a low-temperature transition at 30 degrees higher, the middle transition at 10 degrees higher, and the ferroelectric phase transition occurs at 20 degrees lower than the temperature of the corresponding transitions in single-crystal KTa₀.₅Nb₀.₅O₃.